2006
DOI: 10.1159/000095347
|View full text |Cite
|
Sign up to set email alerts
|

Anencephaly and Pregnancy Outcome in Iran

Abstract: Objectives: The aim of this research is to study the complications of pregnancy associated with anencephaly. Study Methods: Thirty-five mothers who delivered an anencephalic baby (as a case group) and forty-three mothers who delivered a non-anencephalic baby (as a control group)were included in this analytical research study. All cases and controls had singleton pregnancies. More than one matched control was chosen for each case when possible. The cases were selected by a survey of 149,000 births in six educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…This research identified a predominantly young population, which was not significant in other studies (11)(12)(13) . Regarding the duration of pregnancy, preterm birth found in other studies ranged from 50% to 53% meeting the results of this survey, which shows a 55% incidence of this type of delivery.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…This research identified a predominantly young population, which was not significant in other studies (11)(12)(13) . Regarding the duration of pregnancy, preterm birth found in other studies ranged from 50% to 53% meeting the results of this survey, which shows a 55% incidence of this type of delivery.…”
Section: Discussioncontrasting
confidence: 59%
“…The prevalence of polyhydramnios, with a wide variation ranging from 27% to 90%. If we look alone, in our study this was present in 50% of cases (11)(12)(13) . Authors, in their studies found an association between polyhydramnios and congenital anomalies in 81.1% of pregnancies analyzed (14) .…”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations